Oleaginous Microbial Lipids’ Potential in the Prevention and Treatment of Neurological Disorders - Alhattab M; Moorthy LS; Patel D; Franco CMM; Puri M (MDPI (Basel, Switzerland), 2024)
The products of oleaginous microbes, primarily lipids, have gained tremendous attention for their health benefits in food-based applications as supplements. However, this emerging biotechnology also offers a neuroprotective treatment/management potential for various diseases that are seldom discussed. Essential fatty acids, such as DHA, are known to make up the majority of brain phospholipid membranes and are integral to cognitive function, which forms an important defense against Alzheimer’s disease. Omega-3 polyunsaturated fatty acids have also been shown to reduce recurrent epilepsy seizures and have been used in brain cancer therapies. The ratio of omega-3 to omega-6 PUFAs is essential in maintaining physiological function. Furthermore, lipids have also been employed as an effective vehicle to deliver drugs for the treatment of diseases. Lipid nanoparticle technology, used in pharmaceuticals and cosmeceuticals, has recently emerged as a biocompatible, biodegradable, low-toxicity, and high-stability means for drug delivery to address the drawbacks associated with traditional medicine delivery methods. This review aims to highlight the dual benefit that lipids offer in maintaining good health for disease prevention and in the treatment of neurological diseases.
Keywords: neuroprotection; neurological disorders; lipid nanoparticles; oleaginous microbes; omega-3 poly unsaturated fatty acids; lipid neuroprotection